Dampak Psikologis Pernikahan Dini Terhadap Keluarga Harmonis - Tika Nur Azizah; Putri Nurfara Gayanti; Egata Ihsanda Sultan; Prastiwi Dwi Rahmawati; Cantika Alyssa Savitri; Marceliazizah Aning Wendari; Vicky Irawan; Nur Rofiq (Jurnal Budi Pekerti Agama Islam, 2024)
Self-marriage is a big problem in various countries, one of which is Indonesia. Due to this problem, the World Health Organization (WHO, 2021) also emphasizes that delaying the age of marriage can improve family welfare. The aim of this research is to identify the factors that cause early marriage in Indonesia, causing early marriage for perpetrators, children and the surrounding community, various efforts that can be made to prevent and overcome early marriage in Indonesia. This research uses a qualitative approach by collecting various data such as articles and journals on early marriage. Early marriage can occur due to various factors such as economic factors, parental factors, accidents (marriage due to accident), family traditions, local customs. According to the United Nations Children's Fund (UNICEF), early marriage is a marriage carried out officially or unofficially by a person before the age of 18 and has been carried out in various regions. To encourage the current rate of increase in the problem of early marriage, an innovation program was formed, namely the Action of GenRe program. as a promotive and preventive effort against cases of early marriage, it can help teenagers, society and the government in raising healthy and moral teenagers so that it can reduce the occurrence of early marriage.